2018
DOI: 10.1017/psrm.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

A textual Taylor rule: estimating central bank preferences combining topic and scaling methods

Abstract: Scholars o en use voting data to estimate central bankers' policy preferences but consensus voting is commonplace. To get around this, we combine topic-based text analysis and scaling methods to generate theoretically motivated comparative measures of central bank preferences on the U.S. Federal Open Market Commi ee leading up to the nancial crisis in a way that does not depend on voting behavior. We apply these measures to a number of applications in the literature. For example, we nd that FOMC members that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Second, the study of disagreement as the difference in the expressed preferences on specific policy issues and in the salience attributed to them allows us to detect great variation in central bankers’ positions. For instance, it has been found that central bankers express much larger variation in policy positions in speech than they do in votes (Baerg and Lowe, 2020), similar to what happens in other political institutions such as legislatures, political parties and other EU institutions (Hobolt and Wratil, 2018; Proksch and Slapin, 2012; Schwarz et al., 2017). Our semantic distance measure therefore allows us to get closer to the actual disagreement expressed behind closed doors during policy meetings.…”
Section: Studying Disagreement In the Ecb Governing Councilmentioning
confidence: 83%
See 2 more Smart Citations
“…Second, the study of disagreement as the difference in the expressed preferences on specific policy issues and in the salience attributed to them allows us to detect great variation in central bankers’ positions. For instance, it has been found that central bankers express much larger variation in policy positions in speech than they do in votes (Baerg and Lowe, 2020), similar to what happens in other political institutions such as legislatures, political parties and other EU institutions (Hobolt and Wratil, 2018; Proksch and Slapin, 2012; Schwarz et al., 2017). Our semantic distance measure therefore allows us to get closer to the actual disagreement expressed behind closed doors during policy meetings.…”
Section: Studying Disagreement In the Ecb Governing Councilmentioning
confidence: 83%
“…In addition to considering its intuitiveness, we relied on cosine similarity given the purposes of the analysis. Indeed, a measure of similarity based on vectors of word occurrences is the most appropriate technique when the purpose of analysis is to gauge differences in the content and attention that actors devote to specific issues rather than differences in the position of actors on a latent dimension (Benoit, 2019), such as the hawk/dove dimension that is widely used to ascertain central bankers’ preferences (see Baerg and Lowe, 2020). Another practical advantage of cosine similarity is that this measure is not affected by differences in document length.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This paper contributes to the literature by developing a unique approach to measuring the regulatory change that can be used within other contexts outside of finance. We join a growing list of scholars who use text as a new source of data and insights into areas of international political economy as varied as bilateral investment treaties (Arel-Bundock & Lechner 2018), preferential trade agreements (Allee & Lugg 2016), and central bank preferences (Baerg & Lowe 2020).…”
Section: Discussionmentioning
confidence: 99%
“…These tools have been used to explain diverse topics such as MPs' behavior in parliament (Schonhardt-Bailey 2006;Klemmensen et al 2007;Quinn et al 2010;Proksch and Slapin 2012;Eggers and Spirling 2014), policy positions (Laver et al 2003;Slapin and Proksch 2008;Proksch and Slapin 2009), legislator press releases (Grimmer 2010), central bank statements (Baerg 2014;Baerg and Lowe 2015), news reports (Van Atteveldt et al 2008;Coscia and Rios 2012;Stockmann 2012), intra-party divisions (Ceron 2012(Ceron , 2013(Ceron , 2014Greene and Haber 2014;Lo et al 2014), social media (King et al 2013;Barbera 2015) and US government treaties with Native American tribes (Spirling 2012). Alternate approaches to scale the latent preferences of actors' have been particularly useful for some applications in comparative politics research (e.g.…”
mentioning
confidence: 99%